Does the implementation of hardware need software? A longitudinal study on fluoride-removal filter use in Ethiopia - Sonego, Ina L; Huber, Alexandra C; Mosler, Hans-Joachim (Environmental science & technology, 2013)
Evidence suggests that the effectiveness of technology designed to provide safe and healthy water is dependent on the degree of its use. In addition to providing safe water "hardware" (i.e., new infrastructure or equipment) to populations at risk, it might be necessary to also provide suitable "software" programs (behavior change strategies) to support use. A longitudinal survey was conducted in rural Ethiopia following the distribution of fluoride-removal household filters. Three intervention groups were evaluated. Group 1 only received the hardware, i.e., the fluoride-removal filter. Groups 2 and 3 also received software in the form of two evidence-based psychological interventions: a planning and social prompts intervention and an educational workshop with pledging. Group 2 received both software interventions, and Group 3 only received the educational workshop. The effects of the hardware and software on behavior and thus filter use were analyzed along with specific psychological factors. The results showed that the provision of the hardware alone (the fluoride-removal filter) was not enough to ensure sufficient use of the equipment. The addition of a software component in the form of psychological interventions increased filter use up to 80%. An increase in filter use was measured following each intervention resulting in the health-risk being minimized. We conclude that it is necessary that the implementation of hardware of this nature is accompanied by evidence-based intervention software.